Hubungan Dukungan Sosial Keluarga dengan Stres pada Remaja di SMP X Kota Jambi - Khansa Elvina Putri Kuswara; Marlita Andhika Rahman; Hanna Widya Gultom; Agung Iranda (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a developmental period characterized by various biological, psychological, and social changes that may trigger stress. Adolescents face a variety of challenges, including adapting to the school environment, building relationships with peers, and meeting academic demands. This study aimed to determine the relationship between family social support and stress among adolescents at Junior High School X in Jambi City. This study employed a quantitative method with a correlational approach and a cross-sectional design. The sample consisted of 131 adolescents from Junior High School X in Jambi City, selected using a total sampling technique based on the study criteria. Data were analyzed using the Spearman’s rho correlation test. The results showed that the majority of respondents had a moderate level of family social support (84 respondents, 64%) and a moderate level of stress (86 respondents, 66%). The analysis revealed a correlation coefficient of r = −0.396 with a significance value of p = 0.000 (p < 0.05), indicating a significant negative relationship between family social support and stress among adolescents at Junior High School X in Jambi City. It can be concluded that there is a significant negative relationship between family social support and stress among adolescents at Junior High School X in Jambi City. The higher the level of family social support received by adolescents, the lower their level of stress. Conversely, lower levels of family social support are associated with higher levels of stress experienced by adolescents.